Anmeldelser - Maegaard, Jan (Danish Yearbook of Musicology, 1995)
Review of: G.E.F. Weyse: The Late Piano Works. Bohumila ]edlickova (klaver). Dacapo DCCD 9307. J.P.E. Hartmann: Piano Sonatas. Nina Gade (klaver). Dacapo DCCD 9112. Louis Glass: Piano Fantasy, Piano Sonatas. Nina Gade (klaver). Dacapo DCCD 9306. Lange-Müller: Piano Works. Mogens Dalsgaard (klaver). Dacapo DCCD 9206. Peter Arnold Heise: Chamber Music. Amalie Malling (klaver) Morten Zeuthen (cello) The Kontra Quartet. Dacapo DCCD 9113. Rued Langgaard: The Kontra Quartet. Dacapo DCCD 9302 a/b. Danish Golden Age Piano Trios. Tre Musici. Dacapo DCCD 9310.